Metabolic control through glucocorticoid hormones: an update - Rose, Adam J.; Herzig, Stephan (Molecular and cellular endocrinology, 2013)
In the past decades, glucocorticoid (GC) hormones and their cognate, intracellular receptor, the glucocorticoid receptor (GR), have been well established as critical checkpoints in mammalian energy homeostasis. Whereas many aspects in healthy nutrient metabolism require physiological levels and/or action of GC, aberrant GC/GR signalling has been linked to severe metabolic dysfunction, including obesity, insulin resistance and type 2 diabetes. Consequently, studies of the molecular mechanisms within the GC signalling axis have become a major focus in biomedical research, up-to-date particularly focusing on systemic glucose and lipid handling. However, with the availability of novel high throughput technologies and more sophisticated metabolic phenotyping capabilities, as-yet non-appreciated, metabolic functions of GC have been recently discovered, including regulatory roles of the GC/GR axis in protein and bile acid homeostasis as well as metabolic inter-organ communication. Therefore, this review summarises recent advances in GC/GR biology, and summarises findings relevant for basic and translational metabolic research.
Gesehen am 20.01.2022